Efek Magnetooptis Pada Lapisan AgBr Terekspos - Sulistyo, Respita; Firdausi, K. Sofjan; Marhaendrajaya, Indras (BERKALA FISIKA, 2007)
The non linear optic characteristic from several transparent medium (film plate and glass) under influence of external magnetic field and variation of wavelengths, have been identified. In this experiment, the developed AgBr film is deposited on a hologram. The magnetic field has been produced by coils which connected to slide regulator (0-240V). The maximum value of magnetic field is about 182,0 mT. Light sources used are He-Ne Laser with a wavelength of 633 nm and 1 mW in power, and green laser pointer with a wavelength of 532 nm and power less than 5 mW. The optical characteristic measured in this experiment is the rotation of electric field, of the transmitted laser beam due to applied external magnetic field to the medium. The experiment result shows that is dependent linearly on magnetic fields. The Verdet constant is proportional with wavelength of the light. Measured values for Verdet constant (V) at 632,8 nm is (0,487300,00070) min/G-cm and at 532 nm is (0,261700,00056) min/G-cm for glasses material and the values for Verdet constant at 632,8 nm is (0,328500,00060) min/G-cm and at 532 nm is (0,156900,00039) min/G-cm for film plate. Key words:Magnetooptical effect, non linear optic, Verdet constant